Confessions of A Monster
A documentary made in the fall of 1992 in a military prison in Sarajevo, where a group of journalists, including John Barnes of the New York Times, were introduced to Borislav Herak, a young man in JNA uniform, and the first person in fifty years to be charged with the crime of genocide. His confession, full of illustrative details, are almost unfathomable to the human mind and they paint a striking picture of the atrocities committed in Bosnia in the early 1990s.